Anthropometric profile of elite master swimmers - Gattai, G.; Benelli, P.; Ditroilo, M.; Giacomini, F.; Del Sal, M.; Fernandez, E.; Freddo, A.; Grassi, E.; Stocchi, V. (Biomechanics and Medicine in Swimming X, 2006)
In order to define a functional model of Master Swimmer, anthropometric data and upper and lower limb strength were assessed in 54 men and 61 women participants to the 10<h Fina World Master Championships. ANOVA showed age-related significant differences (p<0.05), just in male subjects, concerning Fat Mass (FM%) percentage-increasing and thigh (TV) and forearm (FV) muscle-bone volume decreasing, which may be explained by decreasing of whole muscle mass. Different statistic tendencies among men and women might be due to i) lower muscle mass in females, whereupon the loss is reduced with aging and ii) different loss rate in muscular mass which is gender associated. Significant (p<0.05) strength progressive decrease came up to evidence, for both sexes.